Prevalence of antimicrobial-resistant Escherichia coli infections in diarrhoeic piglets - Loh, Teck Chwen; Lim, H. C.; Bahaman, Abdul Rani; Foo, Hooi Ling (Veterinary Association Malaysia, 2006)

(untitled)
The prevalence of antimicrobial resistance Escherichia coli infection in diarrhoeic piglets was studied. Sixty-five samples were collected from 10 farms in Penang, Perak and Selangor. Escherichia coli isolated from the samples were subjected to antimicrobial sensitivity test. The results showed that Escherichia coli was highly resistant to oxytetracylcine (100%), nalidixic acid (96.8%), trimethoprim-sulfadimthoxine (95.1 %), chloramphenicol (91.9%), enrofloxacin (90.3 %), ampicilllin (85.5 %), kanamycin (74.2 %) and neomycin (71.3 %). However, Escherichia coli was sensitive to apramycin and colistin sulphate. Most of the Escherichia coli isolates showed multiple resistance to the antimicrobials tested in this study.